Identification of alkaloid compounds arborinine and graveoline from ruta angustifolia (L) pers for their antifungal potential against isocitrate lyase (ICL1) gene of Candida Albicans - Sandai, Doblin (Tanjung Malim, 2021)
Identification of alkaloid compounds arborinine and graveoline from ruta angustifolia (L) pers for their antifungal potential against isocitrate lyase (ICL1) gene of Candida Albicans by Sandai, Doblin